2016
DOI: 10.1128/iai.01497-15
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Causes Paralyzing Systemic Necrotizing Vasculitis Driven by Pathogen-Specific Type I Immunity in Mice

Abstract: dInfectious agents are often considered potential triggers of chronic inflammatory disease, including autoimmunity; however, direct evidence is usually lacking. Here we show that following control of acute infection of mice with the myotropic Colombiana strain of Trypanosoma cruzi, parasites persisted in tissue at low levels associated with development of systemic necrotizing vasculitis. Lesions occurred in many but not all organs and tissues, with skeletal muscle arteries being the most severely affected, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 35 publications
5
28
3
1
Order By: Relevance
“…Skeletal muscle of mice chronically infected with T. cruzi is heavily infiltrated with T lymphocytes and mononuclear phagocytes but not neutrophils. Previously, we used flow cytometry to identify CD4 ϩ and CD8 ϩ T cells as well as F4/80 ϩ macro-phages as the main leukocyte subsets infiltrating skeletal muscle during the chronic phase of infection of C57BL/6 mice with the myotropic Colombiana strain of T. cruzi (24). Both CD4 ϩ and CD8 ϩ T cells were highly activated (CD62L Ϫ CD44 hi ) and produced the type I cytokines IFN-␥ and TNF-␣.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle of mice chronically infected with T. cruzi is heavily infiltrated with T lymphocytes and mononuclear phagocytes but not neutrophils. Previously, we used flow cytometry to identify CD4 ϩ and CD8 ϩ T cells as well as F4/80 ϩ macro-phages as the main leukocyte subsets infiltrating skeletal muscle during the chronic phase of infection of C57BL/6 mice with the myotropic Colombiana strain of T. cruzi (24). Both CD4 ϩ and CD8 ϩ T cells were highly activated (CD62L Ϫ CD44 hi ) and produced the type I cytokines IFN-␥ and TNF-␣.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that in C57BL/6 mice chronically infected with the myotropic strain Colombiana, the organism is detected rarely and only in skeletal muscle myocytes; however, parasite DNA can be found in other tissues, including heart and peripheral nerve (24). In heart, there is mild perivascular inflammation in the chronic phase but little if any myocarditis.…”
mentioning
confidence: 99%
“…For example, parasites were detected in the central vein of the adrenal gland in several small autopsy studies at frequencies of 5% [6], 30% [4] and 50% [83]. Progressive multi-organ vasculitis has been reported in mice infected with the high virulence Colombiana (TcI) strain [84]. …”
Section: Elusively Reclusive: T Cruzi In the Chronic Phasementioning
confidence: 99%
“…It is not known how trypomastigotes transit between tissues and the circulation. The trypomastigote surface glycoprotein gp85 does have high avidity for vascular endothelial cells [96] and vasculitis can be a feature of chronic infections [84]. Nevertheless, superinfection experiments indicate that the majority of parasites entering the blood of chronically infected hosts are expected to be rapidly opsonized and cleared, mainly in the liver by Kupffer cells [19].…”
Section: Re-invasion As a Route To Parasite-driven Cardiopathogenesismentioning
confidence: 99%
“…Tais alterações são invariavelmente acompanhadas de intenso infiltrado de células mononucleares, inicialmente composto por macrófagos e neutrófilos, e posteriormente por linfócitos, plasmócitos, eosinófilos e mastócitos (ANDRADE, 1999;MARCON et al, 2011). Granulomas não-necrosantes pode estar presente com células gigantes multinucleadas (ROFFÊ et al, 2016). A destruição de nervos parassimpáticos na região epicárdico-mediastinal tem sido documentada, sugerindo um potencial mecanismo para ocorrência de arritmias e morte súbita (MIRANDA et al, 2011;BONNEY et al, 2019).…”
Section: Variabilidade Genética De T Cruziunclassified